Application of IIA Method and Virtual Bus Theory for Backup Protection of a Zone Using PMU Data in a WAMPAC System - Aníbal Antonio Prada Hurtado; Eduardo Martinez Carrasco; Maria Teresa Villén Martínez; Jose Saldana (Energies, 2022)
Many wide area monitoring, protection, and control (WAMPAC) systems are being deployed by grid operators to deal with critical operational conditions that may occur in power systems. Thanks to the real-time measurements provided by a set of distributed phasor measurement units (PMUs), different protection algorithms can be run in a central location. In this context, this article presents and validates a novel method that can be used as a backup protection for a selected area in a power system. It merges the integrated impedance angle (IIA) protection method with the theory of virtual buses in wide area electrical power systems. The backup protection works this way: once a fault is detected (pickup time), another delay (added to the pickup time) is defined in order to wait for the primary protection to act. If this does not happen, the algorithm generates its backup trip. The proposed method has been called the zone integrated impedance angle (Zone IIA). A real-time PMU laboratory has been used to test the proposed algorithm using a real-time digital simulator (RTDS). The algorithm has been programmed in a real-time automation controller (RTAC). It has been tested in two different simulated setups: first, a 400 kV transmission system, with and without the use of renewable energy sources (RES); second, a 150 kV submarine line between the Greece mainland and an island, which is currently the longest submarine alternating current connection in the world. The results obtained during the tests have yielded tripping times for area protection in the order of 48 ms, if no time delay is used between the fault detection and the trip order. According to the test results, the proposed method is stable, reliable, obedient, and secure, also with RES installed in the power system. Additionally, the method is selective, i.e., during the tests no trip was executed for external faults, no trip was executed in no-fault condition, and all the applied internal faults were detected and tripped correctly. Finally, the protection method is easy to implement. The method is also applicable to protection against short circuits in distribution systems. According to the trip times observed during the tests, it is clear that these algorithms are well suited to implement backup protections in transmission grids, even in scenarios with high penetration of renewable energies. Considering that backup trip times in transmission grids are usually set between 400 and 1000 ms, and that the actuation times obtained by the proposed algorithm are under 100 ms, the method is suitable for its use as a backup protection.